STUDENT FEES STUDIED FOR SPORTS, DRIVER'S ED, AFTER-SCHOOL PROGRAMS: NORTHWEST SPORTS FINAL, NW Edition - Krystyna Slivinski. Special to the Tribune (Chicago tribune (1963), 1997)
Barrington area students may be asked to pick up some of the costs of extracurricular activities such as football and driver's education. However, Edith Auchter, finance committee chairwoman, said it is "highly inappropriate" for the board to provide students with practice clothing. Also, students should pay for such "consumable" items as paper and paints for optional activities, she said.